Detection of MYD88 and CXCR4 mutations in cell-free DNA of patients with IgM monoclonal gammopathies. Issue 12 (December 2018) - Bagratuni, Tina; Ntanasis-Stathopoulos, Ioannis; Gavriatopoulou, Maria; Mavrianou-Koutsoukou, Nefeli; Liacos, Christine; Patseas, Dimitrios; Kanellias, Nikolaos; Migkou, Magdalini; Ziogas, Dimitrios; Eleutherakis-Papaiakovou, Evangelos; Roussou, Maria; Fotiou, Despina; et al.
Abstract Liquid biopsyis being integrated into cancer diagnostics with profound therapeutic implications. However, its role in Waldenström's Macroglobulinemia (WM) and IgM monoclonal gammopathies is still unclear. In this study, we evaluated the role of peripheral blood (PB) cell-free DNA (cfDNA) in characterizing the mutational status ofMYD88 andCXCR4 of patients with IgM monoclonal gammopathies. Paired bone marrow (BM) tumor DNA (tDNA) and PB cfDNA samples from 98 patients (9 MGUS, 45 with WM in remission, 44 with smoldering WM, newly diagnosed or relapsed WM) and 10 controls with non-IgM monoclonal gammopathies were analyzed. Regarding MYD88L265P mutation, 76 patients had paired tDNA and cfDNA informative samples. Among patients with WM in remission, 65% harbored the MYD88L265P mutation, whereas the corresponding percentage among smoldering/newly diagnosed or relapsed WM was 92%. The overall concordance rate was 94% (72/76). For CXCR4 mutations, 65 patients had paired informative tDNA and cfDNA samples. The overall concordance rate was 90% (59/65). All controls had wild-typeMYD88 andCXCR4 . In conclusion, PB cfDNA is a useful, minimally invasive, cost-effective, and time-effective tool for the identification of the presence ofMYD88 andCXCR4 mutations in patients with IgM monoclonal gammopathies avoiding unnecessary BM assessment.